Optimization of Calcination Temperature of Eggshell Catalyst and Palm Oil Biodiesel Production for Blending of B10 Petroleum Diesel Fuel - Abdul Patar, Mohd Affifudin; Nasir, Nurul Fitriah; Osman, Shahrul Azmir; Mat Isa, Norasikin (Penerbit Akademia Baru, 2020)
Palm biodiesel is presently the highlight of current diesel trends, more so in Malaysia. The study of this field is increasing day by day to find ways to reduce its production cost. This study is conducted to analyze the trend of different calcination temperatures to the production of calcium oxide catalyst derived from waste eggshells. The different temperatures are then further analyzed to determine which is the most optimum calcination temperature. Catalyst characterization was conducted by using SEM, XRD and FTIR. It is found that from three different calcination temperatures (900°C, 920°C, 950°C), 920°C is determined to be the most optimum as it gives out the higher yield of calcium oxide while using less energy consumption. The selected optimum catalyst is then utilized to synthesize biodiesel derived from palm olein oil through the process of transesterification. Nine different parameters of transesterification process with different molar ratios and catalyst wt.% content had been conducted and nine different samples are prepared. From these nine samples, one parameter was chosen to be the optimum. Parameters with 12:1 molar ratio, 4wt.% catalyst content, 60°C fixed reaction temperature and 600rpm fixed constant stirring speed are deemed to be the most optimum which yielded 98.89% of biodiesel. This sample is then tested for its properties to determine whether it complies with the ASTM standard before it is blended into petroleum diesel. Properties being tested includes kinematic viscosity, water content, flash point, density and fatty acid methyl ester (FAME) content. The sample is then mass produced to be blended with pure diesel (B0) with fixed ratio of 9:1, in house blend of B10 petroleum diesel fuel is made. The blend was renamed EB10. This biodiesel fuel blend was also tested for its properties to determine if it is safe to be used in consumers vehicles. And it is shown that it is safe to be applied on a daily basis. The blend was also compared to the quality of market available diesel fuel (BHP), and EB10 was proven to have the same quality.